The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/chem.201301498
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Core–Shell Fenton Nanocatalyst: A Mild, Operationally Simple Approach to the Synthesis of Adipic Acid

Abstract: Mesoporous nanoparticles composed of γ-Al2O3 cores and α-Fe2O3 shells were synthesized in aqueous medium. The surface charge of γ-Al2O3 helps to form the core–shell nanocrystals. The core–shell structure and formation mechanism have been investigated by wide-angle XRD, energy-dispersive X-ray spectroscopy, and elemental mapping by ultrahigh-resolution (UHR) TEM and X-ray photoelectron spectroscopy. The N2 adsorption–desorption isotherm of this core–shell materials, which is of type IV, is characteristic of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…379 The most common industrial process for its synthesis involves nitric acid oxidation of cyclohexanol or cyclohexanol-cyclohexanone mixtures. Bhaumik and co-workers have reported mesoporous, crystalline Al 2 O 3 @Fe 2 O 3 CSNs via a new synthetic approach in aqueous medium 381 utilizing the negative charges on the surface of g-Al 2 O 3 for the formation of the CSNs. Bhaumik and co-workers have reported mesoporous, crystalline Al 2 O 3 @Fe 2 O 3 CSNs via a new synthetic approach in aqueous medium 381 utilizing the negative charges on the surface of g-Al 2 O 3 for the formation of the CSNs.…”
Section: Catalytic Applications Of Al 2 O 3 @Fe 2 O 3 Csns For the Symentioning
confidence: 99%
“…379 The most common industrial process for its synthesis involves nitric acid oxidation of cyclohexanol or cyclohexanol-cyclohexanone mixtures. Bhaumik and co-workers have reported mesoporous, crystalline Al 2 O 3 @Fe 2 O 3 CSNs via a new synthetic approach in aqueous medium 381 utilizing the negative charges on the surface of g-Al 2 O 3 for the formation of the CSNs. Bhaumik and co-workers have reported mesoporous, crystalline Al 2 O 3 @Fe 2 O 3 CSNs via a new synthetic approach in aqueous medium 381 utilizing the negative charges on the surface of g-Al 2 O 3 for the formation of the CSNs.…”
Section: Catalytic Applications Of Al 2 O 3 @Fe 2 O 3 Csns For the Symentioning
confidence: 99%
“…The advantage of choosing mesoporous silica as support for incorporating other foreign atoms or functionalities is the inertness of the inorganic silica walls, where tetravalent Si atom can be replaced by the other reactive metal centers retaining considerably good surface area and porosity. 10 Adipic acid is a industrially important dicarboxylic acid, which can be produced exclusively from catalytic oxidation of cyclohexane, cyclohexene or cyclohexanone over mesoporous materials like WO 3 /SiO 2 , 51 and core-shell Fenton catalyst (Fe 2 O 3 /Al 2 O 3 ), 52 respectively in presence of H 2 O 2 oxidant. In Figure 3 step by step formation of adipic acid from these hydrocarbons are shown.…”
Section: Redox Reactions Over Mesoporous Materialsmentioning
confidence: 99%
“…Thus Luo et al reported that the heterogeneous Fenton degradation rate of Rhodamine B using nano particle BiFeO 3 catalyst was about 20 times higher than that obtained with Fe 3 O 4 at pH of 5 at 25°C [12]. Xu and Wang [11] found that the removal rate of 4-chlorophenol in a heterogeneous Fenton reaction was 100% for CeO 2 /Fe 3 O 4 composite catalyst after 120 minutes at a pH of 3, compared with only 5% and 21% for CeO 2 and Fe 3 O 4 catalysts, respectively. Other metals that were incorporated into iron based Fenton catalysts include; Mo (Tian et al), Al (Patra et al) and Ti (Zhong et al) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Having unique properties including high adsorptive and catalytic activities, iron oxides can be manipulated to achieve special physical and chemical structures in order to bring added advantages to the target reactions [9]. Many solid catalysts containing iron like Fe, Fe 2 O 3 , Fe 3 O 4 and FeOOH have demonstrated to be effective in heterogeneous Fenton treatment of various organic pollutants in water [10,11]. In order to enhance their catalytic abilities for decomposing H 2 O 2 to yield powerful radicals other elements are incorporated into iron-containing particles.…”
Section: Introductionmentioning
confidence: 99%